2004
DOI: 10.1080/00365590410018666
|View full text |Cite
|
Sign up to set email alerts
|

Patient Tolerance During Outpatient Flexible CystoscopyA Prospective, Randomized, Double‐blind Study Comparing Plain Lubrication and Lidocaine Gel

Abstract: There are no differences in the perception of discomfort and pain by patients when anesthetic lubricant or simple lubrication are used if the waiting time before the exploration is 5 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…Several studies have evaluated the efficacy of lidocaine gel in regard to the discomfort felt during the instillation of the lidocaine gel before instrumentation, volume of lidocaine used, lidocaine temperature and the time that it was instilled before cystoscopy [13,17,18]. Furthermore, some studies demonstrated no significant difference between lidocaine gel lubrication and plain gel lubrication in decreasing pain and discomfort during cystoscopy [13,19]. Herr and Schneide's study showed no difference in pain relief between cystoscopy performed immediately after lidocaine gel instillation and after 15 min delay [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the efficacy of lidocaine gel in regard to the discomfort felt during the instillation of the lidocaine gel before instrumentation, volume of lidocaine used, lidocaine temperature and the time that it was instilled before cystoscopy [13,17,18]. Furthermore, some studies demonstrated no significant difference between lidocaine gel lubrication and plain gel lubrication in decreasing pain and discomfort during cystoscopy [13,19]. Herr and Schneide's study showed no difference in pain relief between cystoscopy performed immediately after lidocaine gel instillation and after 15 min delay [20].…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of more sophisticated and small caliber flexible cystoscopes, the need for topical lidocaine has been questioned. While several studies have shown that intraurethral anesthetic lubricant reduces pain compared with plain lubrication [2], others have failed in demonstrating any benefit in patient comfort [3]. Furthermore, there is no benefit from waiting a short time between the instillation of lidocaine gel and the insertion of the cystoscope [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cystoscopy has been proven quite successful in surveillance and follow-up of patients with treated bladder cancer. The drawback of cystoscopy is that it is quite expensive, invasive and uncomfortable (6). Urine cytology has been the gold standard for bladder cancer screening and surveillance in the past (7) but it is subjective and requires adequate number of exfoliated cells in the urine, and cellular alterations are likely due to change in collection conditions and therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%